Estabilização de sistemas não lineares com saltos Markovianos - Matsue Filho, Sérgio (2018)
Markov Jump Systems have received notable attention in last few years. For this reason conditions that guarantee stability for a certain type of nonlinear Markov Jump System were developed in this work. Here is presented a real-time application in an automotive valve, thus illustrating the theoretical result developed.